A data-driven microstructural rationale for micro-void nucleation in discontinuous fiber composites. (April 2023) - Agyei, Ronald; Hanhan, Imad; Sangid, Michael D
Despite their high strength-to-weight ratio, short fiber reinforced composites, due to their intrinsically heterogeneous microstructures, exhibit complex mechanical behavior, especially relating to failure. This study explores the dependency of micro-void nucleation on microstructural defects by ranking contributions of competing microstructural metrics, as identified through in-situ X-ray microtomography. Using a Gaussian process framework, six metrics were explored which capture the properties of the closest fiber, the closest fiber tip, the closest pore (proximity and volume), and the local stiffness (using 19 μm and 38 μm neighborhoods). The results demonstrated that less stiff, resin rich areas were more relevant for micro-void nucleation than clustered fiber tips, T-intersections of fibers, or varying porosity volumes. By ranking microstructural configurations and their relevancy to damage, this analysis provides which microstructural metrics can induce micro-void nucleation to help modelers improve failure predictions.